Spatial distribution of foraging in female Antarctic fur seals Arctocephalus gazella in relation to oceanographic variables: a scale-dependent approach using geographic information systems - Guinet, Christophe; Dubroca, L; Lea, Ma; Goldsworthy, S; Cherel, Yan; Duhamel, Guy; Bonadonna, F; Donnay, Jp (Marine Ecology Progress Series, 2001)
The distribution of foraging activity for female Antarctic fur seals was investigated at Cap Noir (49 degrees 07 'S, 70 degrees 45 'E), Kerguelen Island in February 1998. Eleven females were fitted with a satellite transmitter and time-depth recorder. The 2 data sets were combined in order to locate diving activity of the seals. The occurrence of fish in the diet of the seals was investigated by the identification of otoliths in 55 scats collected at the breeding colony during the study period. Oceanographic variables were measured simultaneously by direct sampling and satellite remote sensing. The mesopelagic fish community was sampled at 20 stations along 4 transects, where epipelagic trawls were conducted at night at 50 ni depth. We then investigated, using geographic information systems, the relationship between the spatial distribution of diving activity of the seals and oceanographic variables (sea surface temperature, surface chlorophyll concentration, prey distribution and bathymetry) at the same spatio-temporal scale. An inverse relationship was found between the main fish species preyed on by the fur seals and those sampled in trawl nets. However, diving activity of the seals was significantly related to oceanographic conditions, forage fish distribution and distance from the colony, although these relationships changed with the spatial scale investigated, A probabilistic model was developed for the distribution of diving activity, which predicted where females,should concentrate their foraging activity according to the oceanographic conditions of the year, and where breeding colonies should be located.